2017
DOI: 10.1038/s41598-017-14040-5
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired Heparin Nanosponge Prepared by Photo-crosslinking for Controlled Release of Growth Factors

Abstract: Growth factors have great therapeutic potential for various disease therapy and tissue engineering applications. However, their clinical efficacy is hampered by low bioavailability, rapid degradation in vivo and non-specific biodistribution. Nanoparticle based delivery systems are being evaluated to overcome these limitations. Herein, we have developed a thermosensitive heparin nanosponge (Hep-NS) by a one step photopolymerization reaction between diacrylated pluronic and thiolated heparin molecules. The amoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…The GF delivered by PDGF-BB nanoparticles accelerated the generation of blood vessels, meeting the key requirements of bone regeneration ( d'Angelo et al, 2010 ; La and Yang, 2015 ). Meanwhile, the release of FGF-2 was prolonged by heparin nanosponges and stimulated the growth and differentiation of hBMSCs ( Choi W. I et al, 2017 ; Shin et al, 2014 ).…”
Section: Application Of Heparin For Orthopedic Biomaterials Designmentioning
confidence: 99%
“…The GF delivered by PDGF-BB nanoparticles accelerated the generation of blood vessels, meeting the key requirements of bone regeneration ( d'Angelo et al, 2010 ; La and Yang, 2015 ). Meanwhile, the release of FGF-2 was prolonged by heparin nanosponges and stimulated the growth and differentiation of hBMSCs ( Choi W. I et al, 2017 ; Shin et al, 2014 ).…”
Section: Application Of Heparin For Orthopedic Biomaterials Designmentioning
confidence: 99%
“…A burst release of GF is often seen, losing most of the factors after just hours or a few days [175]. So, although the chemical functionalisation of growth factors is well known to reduce the inherent bioactivity [176][177][178][179], often due to steric hindrance or structural modulation, it has been suggested that covalently bound growth factors can achieve more significant osteogenic differentiation as compared to physically entrapped bioactives due to improved retention over longer periods [59,170,173,174,[179][180][181][182].…”
Section: Controlled Delivery Of Growth Factors and Cellsmentioning
confidence: 99%
“…Various "nanosponges" based on organic/polymeric and inorganic materials been reported [52][53][54][55][56]. These have high volume expansions in addition to being porous [57]. Choi et al, searched for a chemically stable vehicle for the sustained release of various growth factors.…”
Section: Covalent Interactionmentioning
confidence: 99%